Titanium-nickel-steel composite plate for bipolar plate for hydrogen production by electrolysis of water and manufacturing method of titanium-nickel-steel composite plate

By designing a titanium-nickel-steel composite plate, the problems of high cost and insufficient corrosion resistance of titanium bipolar plates are solved, realizing a high-strength and low-cost bipolar plate for hydrogen production by water electrolysis, which is suitable for PEM electrolyzers.

CN119220999AActive Publication Date: 2024-12-31ZHEJIANG JISEN METAL TECH CO LTD

Patent Information

Application Number
CN202411092240.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-09
Publication Date
2024-12-31
Estimated Expiration
2044-08-09

AI Technical Summary

Technical Problem

The titanium bipolar plates in existing PEM electrolyzers are expensive and lack corrosion resistance, making it difficult to meet the demand for efficient hydrogen production.

Method used

A titanium-nickel-steel composite plate is used. By adding a nickel layer between the titanium plate and the stainless steel plate, a composite structure with a thickness ratio of 1 to 10:1 is formed. The nickel layer is used to prevent the reaction between the steel and titanium. Combined with the graphite powder layer and welding fixation, metallurgical bonding is achieved, and a bipolar plate with both high strength and corrosion resistance is prepared.

Benefits of technology

It reduces the manufacturing cost of bipolar plates while improving the strength and corrosion resistance of materials, making them suitable for PEM electrolyzers and meeting the needs of efficient hydrogen production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220999A_ABST
    Figure CN119220999A_ABST
Patent Text Reader

Abstract

The invention discloses a titanium-nickel-steel composite plate for a water electrolysis hydrogen production bipolar plate. The titanium-nickel-steel composite plate for the water electrolysis hydrogen production bipolar plate comprises an upper layer, a lower layer and a lower layer which are sequentially arranged, an intermediate layer; a lower layer; wherein the upper layer is a stainless steel plate layer, the middle layer is a nickel material layer, and the lower layer is a titanium plate layer. The titanium-nickel-steel composite plate for the water electrolysis hydrogen production bipolar plate not only has the corrosion resistance of titanium, but also has the high strength (the tensile strength reaches up to 650 MPa) of alloy steel, and meanwhile, the manufacturing cost is greatly reduced (the cost of the titanium-nickel-steel composite plate is 41 yuan / kg-83 yuan / kg, and compared with 120 yuan / kg of a pure titanium bipolar plate).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of bipolar plates for producing hydrogen by electrolysis of water and preparation thereof, and in particular to a titanium-nickel-steel composite plate for bipolar plates for producing hydrogen by electrolysis of water and a manufacturing method thereof. Background Art

[0002] Hydrogen is considered the most promising, green and clean energy. Hydrogen-to-electricity can achieve efficient conversion, hydrogen has a high energy density and is relatively easy to store, and hydrogen-to-electricity conversion has the potential for large-scale application. PEM hydrogen production is the electrolysis of pure water using wind energy, solar energy, electric energy, etc. to produce hydrogen. Its basic process is that water undergoes a hydrolysis reaction at the positive electrode, hydrogen ions pass through the ordered membrane electrode to reach the negative electrode, electrons are transferred from the positive electrode to the negative electrode through an external circuit, and the hydrogen ions and electrons that reach the negative electrode combine to generate hydrogen. This method uses pure water electrolysis, avoids potential environmental pollution, and is environmentally friendly; the proton exchange membrane has low resistance and gas permeability, which makes its current density, work efficiency and gas purity high; the dynamic response speed is fast, which adapts to the volatility of renewable energy generation.

[0003] The PEM electrolyzer is mainly composed of an anode end plate, a cathode end plate, an anode and cathode diffusion layer, an anode and cathode catalyst layer, and a proton exchange membrane. Figure 1 , where the anode end plate and the cathode end plate are collectively called bipolar plates, which are made of titanium plates with a thickness of about 1.0 mm. Titanium and oxygen have a great affinity. In the air or in an oxygen-containing medium, a dense, highly adhesive, and inert oxide film is formed on the titanium surface, which protects the titanium substrate from corrosion. Even if it is mechanically worn, it will quickly heal or regenerate. It is precisely because titanium has these characteristics that it is very suitable for the manufacture of PEM bipolar plates. In order to obtain a higher hydrogen production rate, the PEM electrolyzer is usually composed of multiple individual electrolyzers stacked in series, so the amount of titanium plates used for bipolar plates is extremely large. Moreover, because titanium is a precious metal, the cost of titanium materials is relatively high.

[0004] In order to solve the problems existing in the above-mentioned prior art, the present invention provides a titanium-nickel-steel composite plate for bipolar plates for hydrogen production by electrolysis of water and a manufacturing method: the prepared titanium-nickel-steel composite plate not only has the corrosion resistance of titanium, but also has the high strength of alloy steel, while the manufacturing cost is greatly reduced. The above-mentioned properties make the titanium-nickel-steel composite plate more suitable for use as a material for manufacturing PEM bipolar plates. Summary of the invention

[0005] The object of the present invention is to provide a titanium-nickel-steel composite plate for a bipolar plate for producing hydrogen by electrolysis of water and a manufacturing method thereof.

[0006] Titanium-nickel-steel composite plate for water electrolysis hydrogen production bipolar plate and manufacturing method of the present invention:

[0007] The prepared titanium-nickel-steel composite plate not only has the corrosion resistance of titanium, but also has the high strength of alloy steel, while the manufacturing cost is greatly reduced.

[0008] A titanium-nickel-steel composite plate for a bipolar plate for producing hydrogen by electrolysis of water, the titanium-nickel-steel composite plate for a bipolar plate for producing hydrogen by electrolysis of water comprising:

[0009] upper layer;

[0010] Middle layer;

[0011] Lower level;

[0012] in,

[0013] The upper layer is a stainless steel plate layer, the middle layer is a nickel material layer, and the lower layer is a titanium plate layer.

[0014] As a further improvement of this solution, the upper layer is a 304 stainless steel plate layer.

[0015] The titanium-nickel-steel composite plate for bipolar plates for hydrogen production by water electrolysis according to claim 1 is characterized in that the thickness of the upper stainless steel plate layer is a and the thickness of the lower titanium plate layer is b, satisfying the quantitative relationship: a:b=(1-10):1.

[0016] As a further improvement of this solution, the thickness of the intermediate nickel material layer is 0.1-0.5 mm.

[0017] A method for manufacturing a titanium-nickel-steel composite plate for a bipolar plate for producing hydrogen by electrolysis of water, characterized in that it comprises the following preparation steps:

[0018] Surface treatment before preparation of S1 composite blank

[0019] Perform surface treatment on the composite surfaces between materials;

[0020] Preparation of S2 composite blank

[0021] The titanium-nickel-steel composite is prepared into a composite blank, and two composite blanks are stacked into a composite blank.

[0022] and,

[0023] A graphite powder layer is arranged between the composite blanks 1 and 2, and the stacking sequence is as follows:

[0024] Titanium-nickel-steel;

[0025] Graphite powder layer;

[0026] Steel-Nickel-Titanium;

[0027] Fixing the composite blanks 1 and 2 by welding;

[0028] S3 vacuum treatment of composite blank

[0029] Vacuum degree reaches 10 -1 Pa, after the vacuum degree reaches the requirement, the exhaust air is closed and sealed;

[0030] S4: heating the composite blank to 1000-1200°C, keeping the temperature until the temperature inside and outside the composite blank is uniform, and then hot rolling it into a composite strip or plate with a thickness of 2.0-6.0 mm;

[0031] In this step, the interface of the (titanium-nickel-steel) composite material after hot rolling is metallurgically bonded due to extrusion, deformation, atomic diffusion, etc., and completely becomes a whole.

[0032] S5: The cooled steel plate is head-tailed and edge-trimmed, and the welding material welded on the edge during the composite billet is removed. At this time, the composite steel strip is separated from the graphite to form two independent composite steel strips;

[0033] S6 removes the oxide scale from the composite strip by processes such as shot blasting, and cold rolls it to the required thickness;

[0034] S7 continuously anneals the cold-rolled composite strip at a temperature of 600-700° C.;

[0035] After S8 annealing, a titanium-nickel-steel composite plate is obtained, wherein the titanium side of the titanium-nickel-steel composite plate can be used as a flow channel of a bipolar plate.

[0036] As a further improvement of the present scheme, the specific surface treatment method of the composite surface in S1 is: use milling and grinding methods to make the interface of the composite material flat and smooth, and completely expose the metallic color, then use acetone or alcohol to remove foreign matter on the flat surface, and seal the side by welding to obtain a composite blank.

[0037] As a further improvement of the present solution, an exhaust hole is provided on the end face of the composite blank 1.

[0038] As a further improvement of the present solution, in S6, the required thickness after cold rolling is 1.0 to 3.0 mm.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] Compared with the prior art, the titanium-nickel-steel composite plate for water electrolysis hydrogen production bipolar plate and the manufacturing method of the present invention have the following beneficial effects:

[0041] 1) In the present invention, one side of the composite plate is a 304 stainless steel plate, the other side is a titanium plate, and there is a pure nickel layer between the steel and titanium. The thickness ratio of steel to titanium is 1 to 10:1, and nickel is the middle layer. The actual thickness of each layer in the composite plate can be adjusted as needed. The higher the proportion of steel, the higher the cost, but the titanium layer is too thin and easy to break. The 304 stainless steel substrate on one side of the steel-titanium composite plate has high structural strength and certain corrosion resistance, while the other side is pure titanium with good corrosion resistance, which can meet the high corrosion resistance requirements of the bipolar plate surface;

[0042] 2) In the present invention, the 304 stainless steel plate has high strength and certain corrosion resistance, which can ensure that the bipolar plate made of the composite plate has higher strength and basic rust resistance than the pure titanium bipolar plate. The pure titanium layer needs to have a certain thickness to ensure that this side has good corrosion resistance, but increasing the thickness ratio of pure titanium will significantly increase the cost of the composite plate. The role of nickel is to separate steel and titanium to prevent the formation of brittle steel-iron intermetallic compounds. Steel and titanium will react at high temperatures to produce a variety of intermetallic compounds. Steel and nickel are infinitely solid-dissolved, and the intermetallic compounds of nickel and titanium have a certain toughness.

[0043] 3) In the present invention, a method for manufacturing a titanium-nickel-steel composite plate for a bipolar plate for producing hydrogen by electrolysis of water is provided, wherein two composite blanks are stacked into one composite blank in the order of (titanium-nickel-steel) and (steel-nickel-titanium), and a layer of graphite powder is evenly spread between the two layers, with a thickness that can separate the metals on both sides. Both sides of the graphite must be steel, otherwise titanium and graphite will react chemically in the subsequent production process to produce brittle titanium carbide. Then, the (titanium-nickel-steel) and (steel-nickel-titanium) are fixed only by welding so that they will not be delaminated during the hot rolling process;

[0044] 4) The titanium-nickel-steel composite plate for water electrolysis hydrogen production bipolar plate of the present invention not only has the corrosion resistance of titanium, but also has the high strength of alloy steel (tensile strength is up to 650MPa), while the manufacturing cost is greatly reduced (the cost of titanium-nickel-steel composite plate is 41 yuan / kg to 83 yuan / kg, compared with 120 yuan / kg of pure titanium as bipolar plate). BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 Schematic diagram of the internal structure of a PEM electrolyzer;

[0046] Figure 2 This is a schematic structural diagram of a titanium-nickel-steel composite billet for a bipolar plate for producing hydrogen by electrolysis of water according to the present invention;

[0047] Figure 3 It is a schematic diagram of the structure of the composite blank (titanium-nickel-steel)-(graphite powder layer)-(steel-nickel-titanium) of the present invention;

[0048] Figure 4This is a schematic diagram of the structure of the exhaust holes on the end face of the composite blank of the present invention, in which the side face is sealed by welding.

[0049] Description of reference numerals:

[0050] 11-Upper level;

[0051] 12-middle layer;

[0052] 13-lower level;

[0053] 20-composite blank;

[0054] 21-composite blank one;

[0055] 22- Graphite powder layer. DETAILED DESCRIPTION

[0056] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described below in conjunction with embodiments:

[0057] The titanium-nickel-steel composite plate for the bipolar plate for producing hydrogen by electrolysis of water of the present invention comprises:

[0058] Upper level 11;

[0059] Middle layer 12;

[0060] Lower level 13;

[0061] in,

[0062] The upper layer 11 is a stainless steel plate layer, the middle layer 12 is a nickel material layer, and the lower layer 13 is a titanium plate layer.

[0063] Specifically, the method comprises the following preparation steps:

[0064] Two composite blanks 21 are stacked into a composite blank 20 in the order of (titanium-nickel-steel) and (steel-nickel-titanium). A thin graphite powder layer 22 is evenly spread between the two layers, the thickness of which is just enough to separate the metal (stainless steel plate layer) on both sides. Then, the (titanium-nickel-steel) and (steel-nickel-titanium) are fixed only by conventional welding. The composite blank is vacuumed to a vacuum degree of 10 -1 Pa, after the vacuum degree reaches the requirement, the exhaust air will be closed and sealed.

[0065] The composite blank is heated to 1100℃, kept warm until the temperature inside and outside the composite blank is uniform, and then hot rolled into a composite coil with a thickness of 2.5mm. After hot rolling, the interface of the (titanium-nickel-steel) composite material is metallurgically bonded due to extrusion, deformation, atomic diffusion, etc., and completely becomes a whole. The cooled steel plate is cut and trimmed, and the composite steel strip is separated from the graphite layer into two independent (titanium-nickel-steel) and (steel-nickel-titanium) composite steel strips.

[0066] The composite strip is descaled by shot blasting and other processes, and then cold rolled to a cold-rolled steel strip with a thickness of 1.0 mm. The cold-rolled composite strip is continuously annealed at a temperature of 650°C. After annealing, the titanium-nickel-steel composite plate is ready for use, and the titanium side can be used as the anode flow channel of the bipolar plate.

[0067] Embodiment 1~5, comparative example 1~3:

[0068] As shown in Table 1, 304 stainless steel with a thickness of 20 mm, pure titanium with thicknesses of 2 mm, 5 mm, 10 mm, 15 mm, and 20 mm, and pure nickel with a thickness of 0.2 mm are respectively used as composite materials for compounding, and the width and length of the materials are 250 mm and 1000 mm, respectively, which are Examples 1 to 5, respectively.

[0069] At the same time, 304 stainless steel with a thickness of 2 mm, titanium with a thickness of 2 mm, and nickel with a thickness of 0.2 mm are used as reference objects, namely Comparative Examples 1 to 3.

[0070] The composite materials are laminated in the order of titanium-nickel-steel. Before lamination, all composite surfaces are processed by milling and grinding to make the interface of the composite materials flat and smooth, and the metal color is fully exposed. Then, foreign matter on the flat surface is removed with acetone, and the side is sealed by welding. Figure 3 As shown, a suction hole is left on the end face of the composite blank.

[0071]

[0072]

[0073] As can be seen from Table 2, the tensile strength of the titanium-nickel-steel composite plates of Examples 1 to 5, the stainless steel of Comparative Example 1, and the titanium of Comparative Example 2 were tested. The results show that the tensile strength of the stainless steel of Comparative Example 1 is as high as 675MPa, and the tensile strength of the titanium of Comparative Example 2 is 500MPa. In Examples 1 to 5, as the thickness ratio of steel to titanium changes from 10:1 to 1:1, the tensile strength gradually changes from 650MPa to 575MPa, which is between steel and titanium, and the higher the proportion of steel, the higher the tensile strength. This provides room for improvement in the process of PEM package electrolysis of water to produce hydrogen, which requires structural weight reduction while needing to withstand hydrogen pressure. The tensile strength of nickel in Comparative Example 3 is 400MPa. Since the thickness ratio is very limited, it has little effect on the structural strength.

[0074] The standard pitting potentials of the titanium-nickel-steel composite plates of Examples 1 to 5, the stainless steel of Comparative Example 1, and the titanium of Comparative Example 2 were tested. The results showed that the pitting potential of the steel side of the composite plate was close to the pitting potential of Comparative Example 1, 0.31V, with a range of 0.27 to 0.30V; the pitting potential of the titanium side was close to the pitting potential of Comparative Example 2, 1.53V, with a range of 1.49 to 1.53V, that is, there is no problem with the titanium side of the composite plate being used as a PEM anode.

[0075] The thickness of titanium in the cold-rolled steel strips of Examples 1 to 5 with a thickness of 1.0 mm was tested. The results showed that the thickness ratio of titanium in the steel plate after cold rolling was basically consistent with the thickness ratio when the blank was combined. As the steel to titanium thickness ratio changed from 10:1 to 1:1, the actual thickness of the titanium layer gradually increased from 0.09 mm to 0.5 mm. Based on this result, the thickness of the titanium layer can be reasonably configured as needed during actual use.

[0076] The current price of 304 stainless steel cold-rolled plate is about 15 yuan / kg, the price of cold-rolled titanium plate is about 120 yuan / kg, and the price of nickel plate is about 205 yuan / kg. According to the weight ratio of each material in the composite plate, and adding the comprehensive composite cost of 15 yuan / kg, the calculated cost of the composite plate in Table 2 is obtained. It can be seen that as the thickness ratio of steel to titanium changes from 10:1 to 1:1, the calculated cost of Examples 1 to 5 gradually increases from 41 yuan / kg to 83 yuan / kg, and the cost is much lower than that of pure titanium as a bipolar plate in Comparative Example 2. It can be seen that the higher the proportion of steel in the composite steel, the lower the cost, but too thin a titanium layer may make it possible to damage the titanium layer during processing and use.

[0077] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent changes made using the present invention are within the patent protection scope of the present invention.

Claims

1. A titanium-nickel-steel composite plate for bipolar plates for hydrogen production by water electrolysis, characterized in that: The titanium-nickel-steel composite plate for the bipolar plate for hydrogen production by electrolysis of water includes the following components which are arranged in sequence: Upper layer (11); Middle layer (12); Lower layer (13); in, The upper layer (11) is a stainless steel plate layer, the middle layer (12) is a nickel material layer, and the lower layer (13) is a titanium plate layer.

2. The titanium-nickel-steel composite plate for bipolar plate for hydrogen production by water electrolysis according to claim 1, characterized in that: The upper layer (11) is a 304 stainless steel plate layer.

3. The titanium-nickel-steel composite plate for bipolar plate for hydrogen production by water electrolysis according to claim 1, characterized in that: The thickness of the stainless steel plate layer of the upper layer (11) is a, and the thickness of the titanium plate layer of the lower layer (13) is b, satisfying the quantitative relationship: a:b=(1-10):

1.

4. The titanium-nickel-steel composite plate for bipolar plate for hydrogen production by electrolysis of water and the manufacturing method thereof according to claim 1, characterized in that: The thickness of the nickel material layer of the middle layer (12) is 0.1-0.5 mm.

5. A method for manufacturing a titanium-nickel-steel composite plate for a bipolar plate for producing hydrogen by electrolysis of water according to any one of claims 1 to 4, characterized in that: The method comprises the following preparation steps: Surface treatment before preparation of S1 composite blank Perform surface treatment on the composite surfaces between materials; Preparation of S2 composite blank (20) The titanium-nickel-steel composite is prepared into a composite blank (21), and two composite blanks (21) are stacked to form a composite blank (20). and, A graphite powder layer (22) is provided between the composite blanks 1 (21) and 2 (21), and the stacking sequence is as follows: Titanium-nickel-steel; Graphite powder layer (22); Steel-Nickel-Titanium; Fixing the composite blank 1 (21) and the composite blank 1 (21) by welding; S3: vacuum treatment of the composite blank (20) Vacuum degree reaches 10 -1 Pa, after the vacuum degree reaches the requirement, the exhaust air is closed and sealed; S4: heating the composite blank to 1000-1200°C, keeping the temperature until the temperature inside and outside the composite blank is uniform, and then hot rolling it into a composite strip or plate with a thickness of 2.0-6.0 mm; S5: The cooled steel plate is head-tailed and edge-trimmed, and the welding material welded on the edge during the composite billet is removed. At this time, the composite steel strip is separated from the graphite to form two independent composite steel strips; S6 removes the oxide scale from the composite strip by processes such as shot blasting, and cold rolls it to the required thickness; S7 continuously anneals the cold-rolled composite strip at a temperature of 600-700° C.; After S8 annealing, a titanium-nickel-steel composite plate is obtained, wherein the titanium side of the titanium-nickel-steel composite plate can be used as a flow channel of a bipolar plate.

6. The titanium-nickel-steel composite plate for bipolar plate for hydrogen production by electrolysis of water and the manufacturing method thereof according to claim 5, characterized in that: The specific treatment method of the surface treatment of the composite surface in S1 is: use milling and grinding methods to make the interface of the composite material flat and smooth, and fully expose the metallic color, then use acetone or alcohol to remove foreign matter on the flat surface, and seal the side by welding to obtain a composite blank (21).

7. The titanium-nickel-steel composite plate for bipolar plate for hydrogen production by electrolysis of water and the manufacturing method thereof according to claim 6, characterized in that: An exhaust hole is arranged on the end surface of the composite blank (21).

8. The titanium-nickel-steel composite plate for bipolar plate for hydrogen production by electrolysis of water and the manufacturing method thereof according to claim 5, characterized in that: In S6, the required thickness after cold rolling is 1.0 to 3.0 mm.

Citation Information

Patent Citations

  • Manufacture method of transition joint for welding titanium alloy and stainless steel component

    CN101391263A

  • Preparation method of titanium-steel composite plate

    CN101992344A

  • Preparation method of titanium-steel single-sided composite board

    CN102773254A

  • Titanium alloy and stainless steel electron beam welding filler material, and preparation process and method thereof

    CN103192195A

  • Pack rolling production method of titanium steel composite board

    CN103817149A

Cited By

  • Production process for preventing grain growth of titanium-steel composite plate

    CN119972795A

  • Titanium frame / titanium plate / titanium frame composite structure for PEM bipolar plate and preparation method of titanium frame / titanium plate / titanium frame composite structure

    CN121781178A